Physical-chemical composition and ensiling potential of Giant Guinea sorghum in six different sowing dates - Mateus, Gustavo Pavan; Crusciol, Carlos Alexandre Costa; Costa, Ciniro (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; p.MsoTitle, li.MsoTitle, div.MsoTitle margin:0cm; margin-bottom:.0001pt; text-align:center; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; font-weight:bold; p.MsoBodyText, li.MsoBodyText, div.MsoBodyText margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The lack of alternative crops for fall-winter cultivation is a drawback in the utilization of agricultural production systems, especialy in regions with dry winters. The purpose of this study was to evaluate the potential of Giant Guinea sorghum (Sorghum bicolor subsp. bicolor guinea race) for forage production, ensiling and plant chemical composition, in different sowing dates. The experimental design was a randomized block, with four replications, and six sowing dates. Although sowing was late, Giant Guinea sorghum showed anticipation in development stages due to sensibility to photoperiod; its dry matter production was low, nevertheless the species presented a better quality of forage mass. Due to the considerable capacity of dry matter production and ensiling potential, this species is a good option.